2022
DOI: 10.3390/toxins14020094
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Bulb D2/D3 Receptor Availability after Intrastriatal Botulinum Neurotoxin-A Injection in a Unilateral 6-OHDA Rat Model of Parkinson’s Disease

Abstract: Olfactory deficits occur as early non-motor symptoms of idiopathic Parkinson’s disease (PD) in humans. The first central relay of the olfactory pathway, the olfactory bulb (OB), depends, among other things, on an intact, functional crosstalk between dopaminergic interneurons and dopamine receptors (D2/D3R). In rats, hemiparkinsonism (hemi-PD) can be induced by unilateral injection of 6-hydroxydopamine (6-OHDA) into the medial forebrain bundle (MFB), disrupting dopaminergic neurons of the substantia nigra pars … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 157 publications
1
8
0
Order By: Relevance
“…However, such behavioral studies cannot be conducted in a unilateral model of dopaminergic deficiency, as the unaffected hemisphere partly fills in for the unilateral deficit. This has already been shown in behavioral studies on olfaction in 6-OHDA rats, in which no signs of hyposmia could be detected ( Ilkiw et al, 2019 ; Alberts et al, 2022 ). However, other NMSs, such as anhedonia or depression, are present in unilaterally lesioned animals ( Ilkiw et al, 2019 ).…”
Section: Discussionsupporting
confidence: 66%
“…However, such behavioral studies cannot be conducted in a unilateral model of dopaminergic deficiency, as the unaffected hemisphere partly fills in for the unilateral deficit. This has already been shown in behavioral studies on olfaction in 6-OHDA rats, in which no signs of hyposmia could be detected ( Ilkiw et al, 2019 ; Alberts et al, 2022 ). However, other NMSs, such as anhedonia or depression, are present in unilaterally lesioned animals ( Ilkiw et al, 2019 ).…”
Section: Discussionsupporting
confidence: 66%
“…It cannot be ruled out that an intrastriatal BoNT-A treatment influences the olfactory abilities by BoNT-A-mediated blockade of transmitter release in structures which are important for smelling. Our group demonstrated an improvement in the olfactory abilities of hemi-Parkinsonian rats after unilateral BoNT-A injection into the CPu [ 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the 6-OHDA-induced hemi-Parkinson model of the rat, our research group could not detect any negative effects of intrastriatal application of BoNT-A on olfactory abilities of the animals. On the contrary, these properties were improved [ 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…These toxins reduce the release of acetylcholine on the nerve terminals and inhibit neuromuscular connection. Seven similar subtypes (A, B, C, D, E, F, G) of BoNTs that act with the hyperactivity of cholinergic nerve terminals for a long time are described [1,2]. It has been shown that botulinum neurotoxin A (BoNTA) is widely preferred in clinical application.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that botulinum neurotoxin A (BoNTA) is widely preferred in clinical application. BoNTs have been used effectively in the treatment of many diseases [2]. However, some undesirable side effects might be seen, in addition to its therapeutic effects.…”
Section: Introductionmentioning
confidence: 99%